Broadband multilayer ceramic chip antenna for handsets - Sim, SH; Kang, CY; Yoon, SJ; Yoon, YJ; Kim, HJ (IEE-INST ELEC ENG, 2002)
A novel broadband and small multilayer ceramic chip antenna has been designed and investigated. The proposed antenna has a small size of 14 x 2.4 x 1 mm(3). A wide bandwidth of 33% (VSWR<2.0) has been obtained and the measured antenna gain has an average value of similar to1.2 dBi. These characteristics make the proposed antenna applicable to future mobile handsets.